The Uniform Boundedness Theorem in Asymmetric Normed Spaces - C. Alegre; S. Romaguera; P. Veeramani (Abstract and Applied Analysis)
We obtain a uniform boundedness type theorem in the frame of asymmetric normed spaces. The classical result for normed spaces follows as a particular case.